An m‐phenylenediamine‐based benzoxazine with favorable processability and its high‐performance thermoset. Issue 18 (28th January 2016) - Ren, Shitong; Yang, Xin; Zhao, Xiaojuan; Zhang, Ying; Huang, Wei
ABSTRACT: A novel aromatic diamine‐based benzoxazine (P‐ m PDA) is successfully synthesized from m ‐phenylenediamine ( m ‐PDA), 2‐hydroxybenzaldehyde, and formaldehyde. The polymerization behavior of P‐ m PDA and the properties of its thermoset are studied. The results indicate that P‐ m PDA owns favorable processability including low polymerization temperature, low liquefying temperature, and wide processing window. Even lower polymerization temperature (polymerization onset temperature as low as 80 °C) can be achieved by the promotion of catalysts. The ring‐opening polymerization of P‐ m PDA first generates polybenzoxazine with N, O ‐acetal‐type structure and arylamine Mannich‐type structure, following which rearrangement from N, O ‐acetal‐type structure to phenolic Mannich‐type structure proceeds at elevated temperature. Furthermore, the polymerized P‐ m PDA shows outstanding performance such as extremely high glass transition temperature ( Tg ) of 280 °C, high char yield above 53% at 800 °C under nitrogen and excellent mechanical property. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43368. Abstract :